Synchronization of Switched Complex Bipartite Neural Networks with Infinite Distributed Delays and Derivative Coupling. (30th May 2013) - Bian, Qiuxiang; Cao, Jinde; Wu, Jie; Yao, Hongxing; Zhang, Tingfang; Ling, Xiaoxu
Abstract : A new model of switched complex bipartite neural network (SCBNN) with infinite distributed delays and derivative coupling is established. Using linear matrix inequality (LMI) approach, some synchronization criteria are proposed to ensure the synchronization between two SCBNNs by constructing effective controllers. Some numerical simulations are provided to illustrate the effectiveness of the theoretical results obtained in this paper.